2015
DOI: 10.1017/s0272263115000248
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Age of Acquisition in Late Second Language Oral Proficiency Attainment

Abstract: The current project examined whether and to what degree age of acquisition (AOA), defined as the first intensive exposure to a second language (L2) environment, can be predictive of the end state of post-pubertal L2 oral proficiency attainment. Data were collected from 88 experienced Japanese learners of English and two groups of 20 baseline speakers (inexperienced Japanese speakers and native English speakers). The global quality of their spontaneous speech production was first judged by 10 native speaking ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 72 publications
3
42
0
Order By: Relevance
“…For example, adult L2 learners likely attain improved comprehensibility (but not necessarily reduced foreign accentedness) in accordance with increased experience (typically measured via length of residence profile), as long as they have high willingness to communicate with native and other non-native speakers (Derwing & Munro, 2013;Saito, 2015b). Whereas such experience effects can be clearly observed in the domains of suprasegmentals (Trofimovich & Baker, 2006) and fluency (Mora & Valls-Ferrer, 2012), it may require a great amount of experience (e.g., 5-10 years of immersion) to refine the sophisticated use of language (i.e., segmentals, lexical richness, grammatical complexity) (Saito, 2015a;Baker, 2010).…”
Section: Measuring L2 Oral Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, adult L2 learners likely attain improved comprehensibility (but not necessarily reduced foreign accentedness) in accordance with increased experience (typically measured via length of residence profile), as long as they have high willingness to communicate with native and other non-native speakers (Derwing & Munro, 2013;Saito, 2015b). Whereas such experience effects can be clearly observed in the domains of suprasegmentals (Trofimovich & Baker, 2006) and fluency (Mora & Valls-Ferrer, 2012), it may require a great amount of experience (e.g., 5-10 years of immersion) to refine the sophisticated use of language (i.e., segmentals, lexical richness, grammatical complexity) (Saito, 2015a;Baker, 2010).…”
Section: Measuring L2 Oral Abilitymentioning
confidence: 99%
“…First, we adopted Lex30 to measure L2 productive vocabulary knowledge, as the test was validated and suggested to tap into the productive mental lexicon (Fitzpatrick & Clenton, 2010). Second, following the standards of recent L2 speech research, we elicited spontaneous speech samples via a timed picture description task (Saito, 2015a(Saito, , 2015bSaito et al, 2016), and assessed two global dimensions of L2 oral proficiencyforeign accentedness (linguistic nativelikness) and comprehensibility (ease of understanding)-and one specific aspect of L2 speech-optimal speech rate (Derwing & Munro, 2009). …”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison studies of the effects of L2 speech production-focused training, L2 speech perception-focused training, and L2 speech production-perception mixed training on both modalities would be thus of future interest. It would be also interesting to replicate the current study with different age groups, such as late versus early L2 learners (Saito, 2015) and children versus adults (Baker et al, 2008); with different learning contexts, such as laboratory versus classroom settings; and with different proficiency levels. The impact of length of instruction and residence in target language countries would be worth investigating as well (Saito & Brajot, 2013;Saito & Hanzawa, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…While research on L2 pronunciation and speech comprehensibility has usually employed some form of picture description task (Derwing and Munro, 2009;Hopp and Schmid, 2013;Isaacs and Trofimovich, 2012;Munro and Mann, 2005;Saito et al, 2015) to elicit extemporaneous speech, other aspects of L2 speech research such as fluency research (Foster and Skehan, 1996;Skehan and Foster, 1999) have demonstrated that the quality of the speech produced is attributed to the nature of a task. The impact of task type on L2 speech performance has been discussed actively in the area of fluency along with accuracy and complexity (e.g., Bygate, 1996;Ejzenberg, 1992;Skehan and Foster, 1999).…”
Section: Role Of Tasksmentioning
confidence: 99%